Comparison of the process of maximum voluntary contraction force recovery and the change of phase angle after eccentric and concentric contraction. - Mizukawa, H.; Nakata, H.; Mishima, T. (Journal of Australian Strength and Conditioning, 2020)
Phase angle (PhA) is an indicator of cellular integrity and is calculated from two types of resistance values (i.e. resistance and reactance) obtained by bioelectrical impedance analysis (BIA). Recently, a few studies have shown that PhA decreases with muscle fatigue. However, it appears that muscle fatigue is different mechanisms between eccentric (ECC) and concentric (CON) contraction. It is not clear that the change of PhA is affected by ECC or CON. Therefore, the aim of this study was to compare the process of maximum voluntary contraction force recovery with the change of PhA after ECC and CON exercise.